2015
DOI: 10.1146/annurev-nutr-071714-034258
|View full text |Cite
|
Sign up to set email alerts
|

CoQ10 Function and Role in Heart Failure and Ischemic Heart Disease

Abstract: Coenzyme Q (CoQ) is an essential lipid of cells present in all cellular compartments. The functions of CoQ in mitochondrial respiration and as an antioxidant are established, although the lipid likely has additional, presently unknown, roles. While the therapeutic utility of CoQ10 supplements is recognized in the rare cases of primary CoQ10 deficiencies, a potential role for CoQ10 supplements in cardiovascular disease, particularly heart failure, has also been studied for over 40 years. This review summarizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 174 publications
0
45
0
5
Order By: Relevance
“…CoQ 10 has attracted great interest in the clinical studies for myocardial function and heart failure (158, 159). CoQ 10 effectively counteracts oxidative damage in IMM and improves mitochondrial efficiency, making myocardium more tolerated to hypoxia/reoxygenation stress (160, 161).…”
Section: Mitochondrial Targets For Cardiovascular Diseases (Cvd)mentioning
confidence: 99%
“…CoQ 10 has attracted great interest in the clinical studies for myocardial function and heart failure (158, 159). CoQ 10 effectively counteracts oxidative damage in IMM and improves mitochondrial efficiency, making myocardium more tolerated to hypoxia/reoxygenation stress (160, 161).…”
Section: Mitochondrial Targets For Cardiovascular Diseases (Cvd)mentioning
confidence: 99%
“…CoQ10 is known as a radical scavenger and antioxidant that is effective on recovery of cardiac function and also relieving fatigue [25]. There is one report on the muscle protection effect by CoQ10 supplementation on exhaustive exercise-induced muscular injury of rats by the evaluation of the concentration changes of enzyme biomarkers, creatinine phosphokinase (CPK) and lactate dehydrogenase (LDH) in plasma [26,27].…”
Section: Study On Protection Of Muscle Cells By the Evaluation Of Cpkmentioning
confidence: 99%
“…The pooled effect size was robust and remained significant in the leave-one-out sensitivity analysis. Subgroup analysis suggested that the impact of statins on plasma CoQ10 concentrations is significant for all 4 …”
Section: Introductionmentioning
confidence: 98%
“…CoQ10 has several important roles in the human body such as: involvement in the biosynthesis of pyrimidine and beta-oxidation of fatty acids [2], modulation of the mitochondrial permeability transition pore [3], acting like a coenzyme for several important enzymatic steps in mitochondrial energy production, inhibition of the oxidation of proteins and DNA [4], stabilizing the membrane and preventing lipid peroxidation [5,6] and modulation the expression of genes [7], or recycling of radical forms of vitamin C and E [8].…”
Section: Introductionmentioning
confidence: 99%